High-temperature friction and wear of Ag/h-BN-containing Ni-based composites against steel - Tyagi R.; Xiong D.S.; Li J.L.; Dai J. (My University, 2025)
In order to attain self-lubrication in a wide range of temperatures, Ni-based powder metallurgy (P/M) composites containing different amounts (8-20 wt%) of Ag were prepared, and their friction and wear characteristics were investigated against AISI 52100 steel at temperatures of 25, 400, and 600 °C. One composite containing 12 wt% Ag and 4 wt% h-BN was also prepared and tested under the same conditions to analyze the effect of addition of h-BN on the friction and wear behaviors. The composites mainly consisted of Ni-based solid solution, free tungsten, Ag, and BN as revealed by XRD and EDS analyses. The friction coefficients and wear rates were found to decrease with increasing temperature and amount of silver. The friction coefficients shown by the composites containing relatively higher amounts of silver were in the range from 0.25 to 0.16 with temperature increasing from RT to 600 °C. The wear rates of the Ag/h-BN-containing composites were approximately an order of magnitude lower than those of the Base Alloy (having no solid lubricant) at all the temperatures. The addition of 4 wt% h-BN resulted in slightly greater friction and wear in comparison to the composites containing only silver. © 2010 Springer Science+Business Media, LLC.